BANTUAN HUKUM BAGI GOLONGAN TIDAK MAMPU DI PENGADILAN AGAMA PADANGSIDEMPUAN - Dermina Dalimunthe; Nurhamida hamidah; Sawaluddin Siregar; Hasiah Sikumbang (Institut agama islam negeri Padangsidimpuan, 2023)
People who are unable and legally illiterate are part of citizens who are entitled to legal aid as one of their constitutional rights. The state has established a fair legal process, and provided Legal Aid Post facilities for disadvantaged groups, especially in the Religious Courts, but the application is not murder in theory and principle of law. Legal facts in the Padangsidempuan Religious Court still lack information about legal aid, causing the provision of legal aid to be not fully ideal.This study used descriptive qualitative research, with an empirical normative legal approach, using primary data and secondary data, data collection techniques were carried out using interview techniques and literature study. The practice of providing legal assistance through the Legal Aid Post at the Padangsidempuan Religious Court has been going well although not entirely ideal, from an administrative point of view it has been well organized but there are a few irregularities, namely the Padangsidempuan Religious Court Posbakum provides legal assistance to all people without the requirement of a certificate of incapacity, this not in accordance with Article 5 paragraph (1) and (2), Article 14 part b of Law NO. 16 of 2011 concerning Legal Aid, Article 22 point 1, 2 PERMA NO.1 of 2014 concerning Guidelines for Providing Legal Aid Services for Poor People in Court, one form of legal aid is non-litigation in accordance with Article 4 paragraph (2) of Law NO. 16 of 2011, this mediation process has not been maximized, it seems just a formality, through outreach, programmed and irrational legal counselling does not exist. The supporting factors are the existence of good synergy between the employees of the Padangsidempuan Religious Court and the legal aid post and the existence of a website. The inhibiting factors are the lack of socialization, human resources, limited facilities and infrastructure, and the culture of the people who are still not aware of the importance of mediation.